Effect of low-temperature plasma treatment on rubber properties - Ďurišová, Silvia; Pajtášová, Mariana; Ondrušová, Darina; Janík, Róbert; Mičicová, Zuzana; Dubec, Andrej; Pagáčová, Jana; Šulcová, Jana; Božeková, Slavomíra; Vavro, Jan; Klepka, Tomasz (Polimery, 2024)
The effect of the distance (0.5 and 5 mm) and exposure time (10 and 30 s) of the atmospheric plasma on the structure and surface properties (contact angle, adhesion) of unvulcanized rubber was examined. FT-IR and SEM were used to assess the structure. After plasma treatment, a higher intensity of the OH and COO- bands was observed, while the intensity of the bands from methylene groups decreased. SEM showed that plasma significantly reduces the size and number of agglomerates, resulting in a more uniform structure. The plasma distance has a significant effect on the surface properties of the rubber, with a better effect achieved at a smaller distance (0.5 mm). In this case, the rubber character changed from hydrophobic to hydrophilic, which is related to the introduction of oxygen species. A greater plasma distance (5 mm), regardless of the exposure time, resulted in a lower adhesion force. The exposure time had no significant effect on the tested rubber properties.